Analysis of The Effect Of The Addition of Fly Ash and Petrsoil on The Soil Shear Strength of The Swamp Area - Indrayani Indrayani .; Andi Herius; Daiyan Saputra; Al Muhammad Fadi (Research Centre of Inorganic Materials and Complexs, 2020)
The existence of irrigation canals greatly supports the production of rice produced, where irrigation channels will be equipped with embankment to protect irrigation channels. Existing soil must certainly be able to withstand shear strength to withstand embankment, while the soil in the South Sumatra region, especially the swamp area has a low shear power so it cannot hold back the shear strength from the embankment. For this reason, it is necessary to research the shear strength of the soil in the swamp area by adding fly ash and petrasoil in order to get the effect of increasing the value of the soil shear strength in the swamp area. The tests consists of the seive analysis, index properties, atterberg limits, soil compaction, and shear strength testing, based on SNI and ASTM. Mixed variations consist of 5, namely: (i) soil + petrasoil; (ii) soil + 10% fly ash + petrasoil; (iii) soil + 15% fly ash + petrasoil; (iv) soil + 20% fly ash + petrasoil; (v) soil + 20% fly ash; all variations without ripening. The test results are obtained that addition of 10% fly ash + petrasoil could be increase the soil cohesion value that is 21.56 Kpa, while the variation of the addition of 20% fly ash + water was obtained the highest value of the shear angle, that is 32.31 Kpa.